Children in the George Moses Horton Branch Library. - Unknown (Forsyth County Public Library, 1927)
Photo made in the 1920s.
Children in the George Moses Horton Branch Library. Library was located in the Chestnut Street YWCA from 1927 to 1930.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Winston-Salem (N.C.); Digital Forsyth; Forsyth County Public Library